Crisis Communication Analysis In Waste Management At Pasar Minggu Market, Bengkulu City - Gayatri Linda Wati; Yanto Yanto; Maryaningsih Maryaningsih (Jurnal Multidisiplin, 2026)
The accumulation of waste at Pasar Minggu Market in Bengkulu City has become an environmental issue that affects cleanliness, public health, and the comfort of trading activities in the market area. This condition is not only caused by the limited availability of waste management facilities but is also related to the lack of effective communication between the government as the environmental management authority and the community and traders as users of public space. This study aims to analyze the crisis communication carried out by the Environmental Agency of Bengkulu City in handling the waste problem at Pasar Minggu Market. The research employed a qualitative approach with a descriptive method to provide an in-depth description of the communication processes involved in managing this environmental crisis. Data were collected through in-depth interviews, field observations, and documentation involving informants from the Environmental Agency, market traders, and local community members around Pasar Minggu Market. The findings indicate that the government’s communication in addressing the waste crisis has not been effective because it tends to use a one-way communication pattern and does not actively involve the community in waste management efforts. In addition, limited waste transportation facilities, inadequate waste disposal infrastructure, and low public awareness of environmental cleanliness further worsen the situation. Therefore, strengthening a more participatory communication strategy is necessary through increased direct socialization, transparent information dissemination, and active involvement of both the community and traders in maintaining the cleanliness of the market environment in a sustainable manner.